ChemInform Abstract: Concepts and Molecular Aspects in the Polypharmacology of PARP‐1 Inhibitors. Issue 35 (August 2016) - Passeri, Daniela; Camaioni, Emidio; Liscio, Paride; Sabbatini, Paola; Ferri, Martina; Carotti, Andrea; Giacche, Nicola; Pellicciari, Roberto; Gioiello, Antimo; Macchiarulo, Antonio
Abstract: Review: [52 refs.